Clinical Studies in the Second Line Setting of Advanced Pancreatic Cancer: Are We Making Any Progress? - Ramfidis, Vassilios S; Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad W (JOP. Journal of the Pancreas, 2012)
Despite the enormous advances in clinical research in oncology, the prognosis of pancreatic carcinoma remains poor. The therapeutic options in this type of cancer are very limited, with modest results at present. In the 2012 American Society of Clinical Oncology (ASCO) Annual Meeting, four interesting trials on the second line treatment of pancreatic cancer were presented. The first study (Abstract #4017) with a phase II design suggested that maintenance therapy with sunitinib, after a complete course of standard first line treatment, was feasible and effective while the second phase I/II study (Abstract #4034) evaluated the role of trabedersen, an agent that inhibits TGF-β2 expression. Finally, the efficacy and toxicity of lapatinib combined with either FOLFOX (Abstract #e14533) or capecitabine (Abstract #e14569) were examined in the second line setting of pancreatic cancer. Image: Therapeutic strategies in unresectable or metastatic pancreatic carcinoma.